2003
DOI: 10.1155/s1023621x03000447
|View full text |Cite
|
Sign up to set email alerts
|

Refined Turbulence Modeling for Swirl Velocity in Turbomachinery Seals

Abstract: A generalized new form of the rotation-sensitive source term coefficient previously proposed by Bardina and colleagues as an extension of the standardk-εturbulence model was developed. The proposal made by Bardina and colleagues focused on rotating flows without significant turbulence generation, and the result was a negative-valued constant coefficient. The new functional form developed here for the coefficient has global as well as local dependence. The new model predictions of laser Doppler anemometry measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…One approach to modify the standard {k -«) model in this regard was tested by Kim and Rhode in Ref. [21]. They reported that the standard {k -e) model gave unsatisfactory predictions for the swirl veloeity in labyrinth cavities, whereas the proposed model extension predicted improved results.…”
Section: Effect Of Turbulencementioning
confidence: 99%
“…One approach to modify the standard {k -«) model in this regard was tested by Kim and Rhode in Ref. [21]. They reported that the standard {k -e) model gave unsatisfactory predictions for the swirl veloeity in labyrinth cavities, whereas the proposed model extension predicted improved results.…”
Section: Effect Of Turbulencementioning
confidence: 99%